CURRENT ISSUES OF EMPLOYMENT, SOCIAL PROTECTION DURING THE PERIOD OF MARTIAL STATE: PRACTICAL ASPECT - Dyban, Maksym (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Objective: analyze practical problems of employment during the legal regime of martial law; investigate the features of concluding an employment contract with military personnel on conscription; consider current issues of social protection of the employee’s family, in particular, a child; identify proposals for solving employment problems in modern conditions in Ukraine. Research methods: during the scientific research, general scientific and special methods were used. In particular, the logical-semantic method was used to formulate problematic issues of employment during martial law. The comparative legal method was used to analyze common and distinctive features of forms of systematization of social legislation, characteristics of the correlation of trends in the further development of systematization of social legislation and employment. When generalizing the classification of tasks and functions of employment, classification, group, system-structural and system-functional methods were used. With the help of special legal and statistical methods, theoretical and practical problems of employment of military personnel were identified. In turn, the structural-logical method was used to determine the possibilities of eliminating the outlined problems and optimizing the systematization of social legislation in Ukraine. Results: іt is argued that the process of employment of a conscript, social protection of this category of employees and their family members has a number of practical problems that require urgent resolution at the level of national legislation. Discussion: the issue of the implementation of constitutional guarantees of the right to work and social protection by a person subject to military service is raised.